Eradication of respiratory tract MRSA at a large adult cystic fibrosis centre. Issue 3 (March 2015) - Hall, H.; Gadhok, R.; Alshafi, K.; Bilton, D.; Simmonds, N.J.
Summary Introduction The prevalence of MRSA in patients with CF is increasing. There is no consensus as to the optimum treatment. Method An observational cohort study of all patients with MRSA positive sputum, 2007–2012. All eradication attempts with subsequent culture results were reviewed. Single vs dual antibiotic regimens were compared for both new and chronic infections. Results 37 patients (median FEV1 58.7 (27.6–111.5)% predicted) were identified, of which 67.6% (n = 25) had newly acquired MRSA. Compared with single regimens, a high proportion of dual regimens achieved MRSA eradication (84.6% vs 50%; p = 0.1) for new infections. Rifampicin/Fusidic acid was associated with high success rates (100% vs 60% for other dual regimens (p = 0.13)). Compared with new infections, chronic MRSA was much less likely to be eradicated (18.2%, p = 0.01). Conclusion Combined antibiotic therapy, particularly Rifampicin/Fusidic acid, is a well-tolerated and effective means of eradicating MRSA in patients with cystic fibrosis.